Green Management: Integrating Environmental Sustainability into Business Operations - Khan G, Mohamed Abbas; Z, Mohammed Yahiya; H, Ameen Basha; Razvi, Syed Shakir (CV Media Inti Teknologi, 2026)
Background of study: Environmental sustainability has become an important concern for modern organizations as environmental challenges such as climate change, pollution, and resource depletion continue to intensify. Businesses are increasingly expected to adopt environmentally responsible practices that reduce ecological impact while maintaining operational efficiency. Green management has emerged as a strategic approach that integrates environmental considerations into business operations, including production processes, resource management, and supply chain activities. Aims and scope of paper: This study aims to examine how green management practices influence environmental performance, operational efficiency, and organizational sustainability in business operations. Methods: The study employed a descriptive research design using both primary and secondary data sources. Primary data were collected through structured questionnaires distributed to 120 employees across three organizations implementing green management practices. Secondary data were obtained from sustainability reports, environmental audits, journals, and corporate records. Data were analyzed using descriptive statistics, including percentages, mean values, and trend analysis, to evaluate environmental performance indicators between 2020 and 2022. Result: The findings show significant improvements in environmental performance following the implementation of green management practices. Energy efficiency increased from 65 in 2020 to 82 in 2022, while waste reduction rose from 10% to 24%. Carbon emissions decreased from 1500 tCO₂ to 950 tCO₂. Employee awareness and support for sustainability initiatives also increased, contributing to improved productivity, cost savings, and stakeholder satisfaction. Conclusion: The study concludes that green management significantly enhances environmental sustainability and organizational performance. Integrating sustainable practices into business operations can reduce environmental impact while strengthening long-term competitiveness and stakeholder trust.